Analysis of the Influence of the Charging Process of an Electrical Vehicle on Voltage Distortions in the Electrical Installation - Dobrzycki, Arkadiusz; Kasprzyk, Leszek; Cetin, Muhammed Sefa; Gencoglu, Muhsin Tunay (Mdpi, 2024)
The noticeable dynamic development of electromobility poses new challenges for the energy industry and users of electric vehicles. One of these challenges is coping with the change in the way we refuel. In the case of electric vehicles, the batteries can also be charged via home electrical installations. The presence of a new, non-linear load with significant power may affect the quality parameters of electricity in this installation and therefore indirectly affect the operation of other loads. In order to investigate the possible impact of the electric vehicle charging process on these parameters, a number of measurements were carried out. This paper presents the results of observing voltage distortions in the installation as a result of the harmonics of the current supplying the AC/DC converter in the vehicle. The test results confirm the compliance of the voltage with the requirements of the standards; however, the large share of current harmonics requires the analysis of the anti-shock protections existing in the installation to ensure that they are effective when currents at higher frequencies flow. The research results may be a guide for designers and users of home electrical installations.
Keywords: electric vehicles; charging process; power quality; total harmonic distortion